Forensic Science On Trial: A Critical Analysis Of Dna Profiling, Polygraph Test, Finger Print Test, And Brain Mapping In The Indian Criminal Justice System (International Journal of Environmental Sciences, 2025)
The increasing reliance on forensic science within the Indian criminal justice system marks a paradigmatic shift from testimonial to scientific evidence. While this development purports to bolster the accuracy and objectivity of criminal adjudication, it simultaneously raises profound concerns relating to the reliability, admissibility, and ethical contours of specific forensic techniques. This research critically examines four pivotal forensic tools, DNA profiling, polygraph testing, fingerprint analysis, and brain mapping, in the context of Indian law, jurisprudence, and evolving legislative frameworks, including the newly enacted criminal laws. Despite the scientific allure of DNA evidence and fingerprint analysis, their use remains fraught with procedural lacunae, infrastructural deficits, and an absence of regulatory oversight. Meanwhile, techniques such as polygraph and brain mapping, though frequently employed during investigations, have been declared inadmissible by the Supreme Court, primarily due to concerns surrounding voluntariness and the right against self-incrimination under Article 20(3) of the Constitution. The incorporation of Sections 349 and 93 in the Bharatiya Nagarik Suraksha Sanhita (BNSS), 2023, and Bharatiya Sakshya Adhiniyam (BSA), 2023, respectively, has expanded the scope of forensic collection and evidentiary admissibility; however, these provisions lack robust procedural safeguards and risk enabling coercive and intrusive investigatory practices. This research argues that forensic science, if uncritically embraced, risks supplanting constitutional protections with technocratic authoritarianism. It advocates for a rights-based, scientifically rigorous, and judicially restrained approach to forensic evidence, anchored in procedural due process, informed consent, and independent regulatory oversight, to prevent miscarriages of justice in the guise of scientific certainty.